Clinical application and developmental direction of free flaps in plastic and reconstructive surgery procedures: a bibliometric analysis - Yin, Xinghao; Hua, Qianqian; Ye, Jiangtian; Xie, Shangjing; Lv, Ruitong; Cai, Leyi; Li, Haixun (Frontiers in Surgery, 2025)
IntroductionAdvancements in microvascular surgical techniques have significantly improved the success rate of free flap transplants, making it a preferred method for repairing postoperative tissue defects caused by tumors, trauma, and infections. Despite numerous clinical studies on free flaps in wound reconstruction, comprehensive bibliometric analyses to systematically review their clinical applications and identify emerging research trends are lacking.MethodsThis study analyzed literature from the Web of Science Core Collection (WOSCC), Pubmed, and Embase databases spanning 2004 to 2025. We examined annual publications, global collaborations, research frameworks, and identified emerging research trends and key keywords.ResultsThe analysis revealed that current research focuses on two core areas: the application of free flaps in reconstructive procedures and the emerging intersection of computer technology with medical and material research.DiscussionThese findings provide valuable insights to guide future scholarly inquiries into the utilization of free flaps in plastic and reconstructive surgery procedures.